2017
DOI: 10.6002/ect.mesot2016.p34
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Low-dose valganciclovir prophylaxis is still under investigation in renal transplant procedures. Our aim was to assess the cost effectiveness of 450 mg versus 900 mg valganciclovir prophylaxis in kidney transplant recipients. Materials and Methods: In this prospective trial, 201 kidney transplant patients were randomized (1:1) to receive 450 mg/d (group 1, n = 100) or 900 mg/d (group 2, n = 101) valganciclovir prophylaxis for the first 6 months after transplant. Patients were studied for incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 64 publications
(38 reference statements)
1
6
1
Order By: Relevance
“…The frequencies of CMV DNAemia (3.4%) and syndrome (1.1%) were comparable 8,18 or lower 12,19 than previously reported, which may be related to relatively less ATG use and more liberal immunosuppression in our cohort. However, increased incidence of late CMV infection post-SD prophylaxis was also observed in other studies comparing SD prophylaxis to preemptive treatment, 20 and has been hypothesized to be due to lack of opportunistic low-level CMV DNAemia that could stimulate T-cell immunity and thus prevent downstream late-onset infection and graft rejection.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The frequencies of CMV DNAemia (3.4%) and syndrome (1.1%) were comparable 8,18 or lower 12,19 than previously reported, which may be related to relatively less ATG use and more liberal immunosuppression in our cohort. However, increased incidence of late CMV infection post-SD prophylaxis was also observed in other studies comparing SD prophylaxis to preemptive treatment, 20 and has been hypothesized to be due to lack of opportunistic low-level CMV DNAemia that could stimulate T-cell immunity and thus prevent downstream late-onset infection and graft rejection.…”
Section: Discussionsupporting
confidence: 69%
“…We identified 5 published studies in intermediate-risk kidney transplant recipients: 3 involved 6-month prophylaxis, 8,10,14 and the other two involved 3-month prophylaxis, 12,13 one of which did not adjust for confounders. 13 All aforementioned reports indicated that the effectiveness of LD-VGC was at least comparable to that of SD-VGC prophylaxis, in agreement with our findings and those of two recent meta-analyses with direct or indirect comparisons between SD and LD-VGC prophylaxis, 9,17 one that focused specifically on intermediate-risk kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our study was not powered to detect significant differences in the incidence of PVAN, the rates were clinically not negligible with 3 cases of graft loss directly related to PVAN in the valganciclovir group. Also in a recently published study, full dose valganciclovir prophylaxis resulted in higher rates of PVAN [ 37 ]. It is conceivable that valganciclovir had an effect on the BKV-specific cellular immune response making BKV replication more frequent [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%